Characterization of free and glycosidically bound volatile compounds from tamarillo (Solanum betaceum Cav.) with considerations on hydrolysis strategies and incubation time. (April 2020) - Chen, Xiao; Quek, Siew Young; Fedrizzi, Bruno; Kilmartin, Paul A.
Abstract: Two different hydrolysis strategies, namely acid hydrolysis (pH 0 and 3) and enzyme hydrolysis (Rapidase AR2000, β-glucosidase, 5.6 nkat/mg), and the effect of hydrolysis time on the liberation of glycosidically bound volatiles from tamarillo ( Solanum beaceum Cav.), were evaluated. Free and bound volatile profiles in tamarillo were also compared. Enzymatic hydrolysis was favoured for the liberation of aldehydes, esters, and terpenes. Harsh acidic hydrolysis (pH 0) was particularly effective at releasing C13 -norisoprenoids including 3-hydroxy-β-damascone and 1, 1, 6-trimethyl-1, 2-dihydronaphthalene (TDN), but those compounds cannot contribute to the pleasant odour. Moreover, the longer the duration of enzymatic hydrolysis, the higher was the concentration of alcohols, terpenes, benzenoids, ketones, and volatile phenols. On the other hand, 33 free and 49 bound volatiles were identified in tamarillo with a complementary profile: the major free volatiles were alcohols ((Z)-3-hexenol, 1-hexanol) and esters (methyl caproate, methyl butanoate and ethyl butanoate), while bound volatile compounds showed higher concentrations of benzenoids (benzyl alcohol and phenylethyl alcohol) and terpenes, including prenol, linalool and α-terpineol. Many glycosidically bound volatiles are available as aroma reservoirs in tamarillo, and to liberate these compounds during tamarillo-based product development, attention should be given to hydrolysis strategies and incubation time. Highlights: Glycosidically bound volatiles of tamarillo fruits were identified. Enzymatic hydrolysis shows advantages on the release of bound volatiles. 48 h hydrolysis is favourable for liberation of alcohols, terpenes, benzenoids, ketones, and volatile phenols. Forty-nine glycosidically volatiles are reported for the first time in Solanum betaceum.